Working capital management and SMEs profitability: Portuguese evidence. Issue 3 (1st June 2015) - Pais, Maria Amélia; Gama, Paulo Miguel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to provide empirical evidence on the effects of working capital management on the profitability of small and medium-sized Portuguese firms. Design/methodology/approach – Panel regressions (fixed effects) and instrumental variables were used to model a sample of 6, 063 Portuguese small and medium-sized firms (SMEs), covering the time period 2002-2009. Also, industry-demeaned values and industry-specific dummy variables allow for industry-specific effects robustness tests. Findings – Results indicate that a reduction in the inventories held and in the number of days that firms take to settle their commercial liabilities and to collect payments from its customers are associated to higher corporate profitability. Similar results are obtained when industry-specific effects are controlled, supporting the robustness of the previous analysis. The relevance of quadratic dependences of the profitability on some variables was also identified and suggests a decreasing trend of return on assets with increasing values of the working capital management characteristic variables. Practical implications – The practice of more aggressive working capital management policies increase firms' profitability. Moreover, the importance of a good practice in working capital management is stressed by the evidence suggesting the existence of an optimal level for the working capital components. Originality/value – The consensus that SMEs play a crucial role in the development of the national economy, the lack of published industry wide studies of this type for the case of Portugal, justifies the importance of the present study.